Integrasi Teknologi Pertanian dalam Peningkatan Produktivitas Pangan dan Implikasinya terhadap Kesehatan Masyarakat Indonesia: Sebuah Tinjauan Literatur - Iwan Patria; Melda Emilya; Liza Liza (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the role of agricultural technology in improving food crop productivity and its impact on national food security and public health in Indonesia. A literature review approach was employed by examining relevant national and international scientific publications related to agricultural mechanization, precision agriculture, superior crop varieties, and modern irrigation systems. The findings indicate that the application of agricultural technology significantly improves farming efficiency, reduces post-harvest losses, and increases both the quantity and quality of food crop production. Increased productivity plays an important role in strengthening national food security through enhanced food availability, stability, and accessibility. Moreover, improved access to sufficient and nutritious food contributes to better nutritional status and overall public health outcomes. Despite these positive impacts, the adoption of agricultural technology in Indonesia still encounters several challenges, including limited access for smallholder farmers, unequal regional implementation, inadequate human resource capacity, and insufficient policy and financial support. These constraints may hinder the optimal utilization of technology and limit its broader benefits for food security and public health. Therefore, integrated policies and strong cross-sector collaboration between agriculture, health, and development sectors are essential to ensure that increased food productivity effectively translates into improved community welfare and sustainable development.